Peran Guru Bimbingan Konseling Dalam Meningkatkan Disiplin Siswa Di SMA Negeri 1 Maumere - Fransiskus Eduwart Taping; Ichsan Anshory (Jurnal Kebijakan dan Pengembangan Pendidikan, 2015)
Abstract: This study aims to determine the role of counseling guidance teachers in improving student discipline in Maumere 1 High School. This research uses descriptive qualitative research methods. This research was conducted at Maumere 1 Public High School. Data obtained through interviews, observations, and documents, then systematically described to produce a conclusion in the form of the role of counseling guidance teacher in improving student discipline by the mandate of the Ministry of Education and Culture No. 111 of 2014. The results showed that counseling guidance teachers played a role in disciplining in SMA Negeri 1 Maumere by giving outreach to parents/guardians of students, giving examples of discipline, recording the implementation of student discipline in the consultation book. parents play a role in supporting the disciplinary program by encouraging students and advising them if they violate the rules of conduct at SMA Negeri 1 Maumere. Factors inhibiting the implementation of discipline: Lack of parental motivation towards students in obeying discipline, Differences in students' maturity in responsibilities in school, especially in school discipline, Lack of teacher motivation towards students, especially in implementing school order. Supporting factors include The existence of the school code of conduct for students, a socialization of the code of conduct to parents or guardians of students.Keywords: Counseling Guidance, Student Discipline, Teacher Abstrak: Penelitian ini bertujuan untuk mengetahui peran guru bimbingan konseling dalam meningkatkan disiplin siswa di SMA Negeri 1 Maumere. Penelitian ini menggunakan metode penelitian deskriptif kualitatif. Penelitian ini dilaksanakan di SMA Negeri 1 Maumere. Data diperoleh melalui wawancara,observasi dan dokumen, kemudian diuraikan secara sistematis untuk menghasilkan suatu kesimpulan berupa peran guru bimbingan konseling dalam meningkatkan disiplin siswa sesuai dengan amanat permendikbud No 111 tahun 2014. Hasil penelitian menunjukkan bahwa guru bimbingan konseling berperan dalam penegakan kedisiplinan di SMA Negeri 1 Maumere dengan memberikan sosialisasi kepada orang tua / wali murid, memberikan contoh kedisiplinan, mencatat pelaksanaan kedisiplinan siswa dalam buku konsultasi. orang tua berperan mendukung program kedisiplinan dengan memberikan dorongan kepada siswa dan menasehati apabila melanggar tata tertib di SMA Negeri 1 Maumere. Faktor penghambat pelaksanaan kedisiplinan: Kurangnya motivasi orang tua terhadap siswa dalam mentaati tata tertib, Perbedaan kematangan siswa dalam tanggung jawab di sekolah terutama dalam tata tertib sekolah, Kurangnya motivasi guru terhadap siswa terutama dalam pelaksanaan tata tertib sekolah. Faktor pendukung diantaranya: adanya tata tertib sekolah bagi siswa, adanya sosialisasi tata tertib kepada orang tua wali murid.Kata Kunci: Bimbingan Konseling, Disiplin Siswa, Guru